Integrating Vocational Education and Industry through Public Policy: Towards Excellent and Competitive Human Capital - Riki Satia Muharam; Ufa Anita Afrilia; Sudarma Sudarma (Information Technology and Science (ITScience), 2025)
Vocational education plays a strategic role in developing excellent and competitive human resources (HR) amidst the dynamics of the Fourth Industrial Revolution (Industry 4.0) and Society 5.0. However, challenges such as the mismatch between graduates' competencies and industry needs, the limited involvement of industry in curriculum development, and weak institutional synergy remain major obstacles. This study aims to examine the ideal form of integration between vocational education and the industrial sector, the role of public policy in supporting this integration, and its contribution to the creation of competent and adaptive human resources. A descriptive qualitative approach was employed through literature review and policy analysis. The findings indicate that effective integration can be achieved through five key approaches: co-design, co-teaching, co-training, co-assessment, and co-recruitment. Public policy plays a crucial role as both facilitator and regulator in establishing a collaborative and labor market-oriented vocational–industry ecosystem. The implementation of policies such as Presidential Regulation No. 68/2022, the Center of Excellence Vocational High School (SMK PK) program, and the Pre-Employment Card (Kartu Prakerja) initiative has shown positive impacts on improving graduate quality and workforce absorption. This integration also contributes to enhanced employability, digital literacy, innovative capabilities, and global work readiness. The study concludes that strengthening vocational–industry integration, supported by adaptive and sustainable public policies, is key to building excellent, productive, and globally competitive human resources in Indonesia.